1999
DOI: 10.1002/(sici)1099-0518(19990915)37:18<3614::aid-pola9>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and curing mechanism of epoxy and boron trifluoride monoethyl amine complex system

Abstract: ABSTRACT:The kinetics of cationic polymerization of epoxy resin has been studied. Due to multiple reaction exotherms and irregular baselines involved in this system, the ASTM E 698 method was chosen to determine the kinetic parameters of this epoxy/ BF 3 -MEA system. The DER 332/BF 3 -MEA system follows the first order active chain end (ACE) reaction mechanism. The adding of the hydroxyl group into the system is prone to decrease the activation energy and shifts the curing into the activated monomer (AM) mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The kinetics of epoxy–amine reactions has been well established in the literature 17–21. In the DSC curve of dynamic curing for the DGEBA/MP system, at a heating rate of 10°C/min as shown in Figure 2, T i (199.2°C) is the initial temperature of the curing reaction, T p (244.8°C) is the peak maximum temperature, and T f (276.4°C) is the final temperature, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The kinetics of epoxy–amine reactions has been well established in the literature 17–21. In the DSC curve of dynamic curing for the DGEBA/MP system, at a heating rate of 10°C/min as shown in Figure 2, T i (199.2°C) is the initial temperature of the curing reaction, T p (244.8°C) is the peak maximum temperature, and T f (276.4°C) is the final temperature, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…DCPD are 11,000-14,000 cP and 1 cP, respectively, at room temperature. (63)(64) Even at low DCPD conversions, the system may be diffusion-limited at high concentrations of the epoxy resin components.…”
Section: Effect Of Dilution On the Dcpd Curing Kineticsmentioning
confidence: 99%
“…However, the reaction between epoxy and secondary hydroxyl functionalities is controversial. Whereas Tackie and Martin and others22, 23 claimed that the secondary hydroxyl functionalities on the epoxy chain are less reactive than the epoxy functionalities and do not react below 230 to 270°C, Li et al and other authors24–26 found hydroxyl functionality no less reactive than the epoxy functionality and so did not neglect its participation in the homopolymerization reaction. If the participation of the secondary hydroxyl groups is negligible, the homopolymerization must result in essentially linear polymerization of the epoxy oligomers.…”
Section: Discussionmentioning
confidence: 97%
“…Simplified representations of epoxy resin and MDSA molecules are used. (Note: In homopolymerization, reaction between epoxy and secondary hydroxyl group is also possible but its occurrence is controversial 22–26…”
Section: Discussionmentioning
confidence: 99%